Export strategy competitive advantage in alliance - Loh, Fook Meng (2010)
With the current recession in Asia, many Asian companies are seeking to expand their exports to the highly lucrative markets. But can Asian companies stand up to the competition in the highly sophisticated and competitive global markets? Where is their competitive advantage? Michael Porter's "diamond" model, highlighted in "The Competitive Advantage of Nations" was selected as the framework for this dissertation after a thorough review of the literature. Based on Porter's model, companies with true international competitive advantage are based in only a few advanced nations. It will not be easy for emerging countries in Asia to individually achieve international competitive success due to inherent weaknesses in one or more facets of their national "diamond" caused by historical and natural constraints. However, Porter's model may have under-estimated the importance of the human factor, the role of governments especially in Asia as well as the influence of regional and global effects. There is a strong possibility for Asian countries to leverage on the strength of each other in the pursuit of the regional competitive advantage - perhaps through strategic alliances.